P − V criticality and Joule-Thomson expansion of Hayward-AdS black holes in 4D Einstein-Gauss-Bonnet gravity - Ming Zhang (Elsevier, 2021)
In this paper, the P−V criticality and Joule-Thomson Expansion of Hayward-AdS black holes in 4D Einstein-Gauss-Bonnet gravity are studied in the extended phase space. We find the black hole always exhibits a phase transition similar to that of the Van der Waals system for any arbitrary positive parameters α and g. We also study the dependence of α and g on the inversion curves and plot the inversion and isenthalpic curves in the T−P plane, which can determine the cooling-heating regions.